AGROBIOLOGICAL AND ECONOMIC POTENTIAL OF WINE GRAPEVINE CULTIVARS GROWN IN THE KYUSTENDIL REGION, BULGARIA - Krumov, Simeon (Journal of Agricultural Sciences (Belgrade), 2025)
A comparative analysis of the agrobiological and economic potential of 2 white ('Slava' and 'Droujba') and 3 red ('Kaylashki rubin', 'Trapezitsa' and 'Rubin') wine grapevine cultivars under the soil and climatic conditions of the Kyustendil region of Bulgaria was carried out. Comparative variants (standards) for red cultivars are 'Pamid', and for white cultivars - 'Tamyanka'. The study was conducted during the period 2021-2024 in a collection vineyard of the Institute of Agriculture – Kyustendil, Bulgaria. In terms of quality, fertility and size of the clusters and berries, the studied cultivars reach and even exceed the values characteristic for each of them. The percentage of berries in the cluster was "high" in all variants - from 95.0% for 'Trapezitsa' to 97.2% for 'Kaylashki rubin' and 'Droujba'. The grapes of the 'Pamid' and 'Tamyanka' standards, as well as the interspecific cultivars 'Droujba' and 'Kaylashki rubin', was distinguished by a “very high” theoretical yield. In economic terms, the best results, according to the conditions of the experiment, were achieved with the red cultivars 'Trapezitsa' and 'Kaylashki rubin'. The high level of net income and the rate of profitability determine the presence of significant economic potential in the white cultivar 'Droujba' as well.
Keywords: wine grape cultivars, yield, economic evaluation